IN SEARCH OF IDENTITY: IS EARLY CHILDHOOD EDUCATION A MAN'S PLACE? - Rodrigues, Silvia Adriana; Manholer, Estefania; Gomes, Alberto Albuquerque [UNESP] (Univ Estadual Paulista-unesp, Fac Ciencias Letras Assis, 2020)
This article, which aims to discuss the male presence in the teaching profession, specifically in the space of Early Childhood Education, was organized with data obtained in a qualitative research, which investigated how different school actors understand the social role of daycare centers and professionals that act on it. In this way, information obtained with a student in the Pedagogy course is brought up for discussion, using reports of the practice. The data, treated in the perspective of the analysis of the Bahtinian discourse, lead us to the statement that male harshness is an element of culture and not of human nature - of the male gender. Thus, it is possible, reasonable and acceptable to men to identify with the teaching work at the daycare center; as well as that they are able to build the necessary skills/knowledge (patience, calm, social tact, sensitivity, etc.) for the proper professional performance with the children of this level of education
Keywords: Masculinities and teaching; Professional identity; Teaching in the daycare center